IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN PRESTASI BELAJAR IPA MATERI SISTEM REPRODUKSI MANUSIA - Cucu Heryawati; Sutarya Saputra (Bajang Institute, 2023)
The aim of the research is to improve science learning achievement on human reproductive system material through the STAD Type Cooperative learning model. This research uses the Classroom Action Research (PTK) method which is carried out in two cycles with four stages, namely planning, action, observation and reflection. The subjects in this research were grade 9 students at SMP Negeri 2 Tambun Utara carried out in semester 1 of the 2019/2020 academic year, involving 30 students. The object of the research is science learning achievement regarding the human reproductive system through the implementation of the STAD Type Cooperative learning model. The research instrument is a written test. Data analysis uses comparative descriptive analysis techniques with percentages. The results of this research indicate that there has been an increase in students' science learning achievement regarding the human reproductive system material seen from the average score.